The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1115/1.2895477
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Robotics Technology to Study Human Joint Kinematics: A New Methodology

Abstract: Robotics technologies have been modified to control and measure both the force and position of synovial joints for the study of joint kinematics. One such system was developed to perform kinematic testing of a human joint. A 6-axis articulated robotic manipulator with 6 degrees of freedom (DOF) of motion was designed and constructed; a mathematical description for joint force and position was devised; and hardware and software to control forces applied to the joint, as well as position of the joint, were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(121 citation statements)
references
References 0 publications
4
111
0
2
Order By: Relevance
“…However, existing test apparatuses are either designed for a maximum of two independently controlled DOF with high loading rates [23] or six DOF with low loading rates which allow quasi-static flexibility measurements of spinal motion segments [28][29][30][31][32][33][34][35][36][37][38]. Only two dynamic systems with six DOF are known to the authors: a robotic system by Fujie et al [39], later used for spinal segments by Hurschler et al [40] and a hexapod system by Ding et al [41], designed to be suitable for all biomechanical joints and tissues, including spine [42]. The robotic system (KR 16, Kuka Robotik GmbH, Gersthofen, Germany) used by [40] is able to achieve very rapid motion ranging from 156 to 614°/s depending on the axis, while loads are limited to about 160 N. The custom designed hexapod system by Ding et al [41] is capable of very high loads (up to 21 kN and 2.5 kNm).…”
Section: Introductionmentioning
confidence: 99%
“…However, existing test apparatuses are either designed for a maximum of two independently controlled DOF with high loading rates [23] or six DOF with low loading rates which allow quasi-static flexibility measurements of spinal motion segments [28][29][30][31][32][33][34][35][36][37][38]. Only two dynamic systems with six DOF are known to the authors: a robotic system by Fujie et al [39], later used for spinal segments by Hurschler et al [40] and a hexapod system by Ding et al [41], designed to be suitable for all biomechanical joints and tissues, including spine [42]. The robotic system (KR 16, Kuka Robotik GmbH, Gersthofen, Germany) used by [40] is able to achieve very rapid motion ranging from 156 to 614°/s depending on the axis, while loads are limited to about 160 N. The custom designed hexapod system by Ding et al [41] is capable of very high loads (up to 21 kN and 2.5 kNm).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigators have used robotically simulated Lachman's tests of pure anterior drawer to quantify ACL mechanics in the same fashion that the current study evaluates rotational perturbations [5]. Furthermore, the present results maintain clinical relevance because each stimuli is tested individually, but also in conjunction with one another, which is more representative of the [17,18]. However, previous investigations have indicated that the average ACL ruptures at 19% ± 10% strain, whereas individually these failures occur between 7% and 36% [32].…”
Section: Discussionmentioning
confidence: 73%
“…For example, the Oxford rig [27] allows cadaver joints to be loaded by a single actuator to simulate the quadriceps but does not allow dynamic testing. A system by Fujie et al [28] moves a cadaver slowly using a robot arm, taking measurements throughout. The results here show that these simplifications could significantly change the forces acting within the joint.…”
Section: Discussionmentioning
confidence: 99%